Analisis Keunggulan Bersaing Pada Kinerja Penjualan PT. Abdillah Sukses Bersama - Bima Bima; Deby Ardea; Egha Putra Pramana; Indah Noviyanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze the effect of competitive advantage on the sales performance of PT Abdillah Sukses Bersama. The purpose of this study is to identify the strengths, weaknesses, opportunities, and threats of PT Abdillah Konveksi. In addition, this study discusses the various strategies used by Abdillah Konveksi to improve their sales performance. In this study, the author collected data through interviews and observations. The results showed that Abdillah Konveksi is in a fairly good condition compared to its competitors' convection positions, each of which has its own characteristics and advantages. Abdillah Konveksi is also able to take advantage of opportunities from the problems that exist in the Bangka Belitung Islands. One of the famous convections in Bangka Belitung, PT Abdillah Sukses Bersama, emerged as a result of the most appropriate initial strategy, which focuses on promotional strategies to publicize and build the brand. Keyword: , , and